South Australia : typical city and country views. ([Adelaide] : [Publisher not identified], 1920)
A large format souvenir collection of photographic reproductions, each bordered in gold, with descriptive captions. Subjects include King William Street, North Terrace East, North Adelaide, the Pumping Station at Merbein, North Terrace, Victoria Square West, Children's Hospital, etc. Many of the views are in a panoramic format; of the other images, a small number of postcard format views have captions in the image in white lettering; a small number have a ‘Government photo.’ attribution, and two near the end are attributed to ‘J.B.S.’
Cover title.
Keywords: South Australia -- Description and travel -- 1901-1950.; Australian